Annulation of a 1,3-dithiole ring to a sterically hindered o-quinone core. Novel ditopic redox-active ligands - Norkov, Sergey V.; Cherkasov, Anton V.; Shavyrin, Andrey S.; Arsenyev, Maxim V.; Kuropatov, Viacheslav A.; Cherkasov, Vladimir K. (Beilstein Journal of Organic Chemistry, 2021)
The fused 1,3-dithiole spacer seems to be very suitable for the functionalization of sterically hindered o-quinones with additional groups capable of coordination of metal ions and/or possessing a redox activity. An effective method for the synthesis of sterically hindered o-quinones containing 1,3-diketonate, dinitrile and p-quinone-methide functional groups at the periphery of the ligand has been developed. The novel compounds have rigid and conjugated structures and exhibit properties typical of o-quinones. A study of their monoreduced semiquinone derivatives reveal that the spin density is delocalized across the whole molecule, including peripheral fragments. The first stable o-quinone derivative bearing an annulated thiete heterocycle has been isolated and characterized.
Keywords: dioxolene ligand; 1,3-dithiole; ditopic ligand; o-quinone; thiete